Fishers’ Cultural Funds of Knowledge and Translanguaging Praxis for the Development of Contextualized Instructional Material: A Narrative Ethnography - Joefry Q. Barcebal (PT FORMOSA CENDEKIA GLOBAL, 2023)
The implementation of K to 12 curriculum in coastal villages in the Philippines posed a pressing concern on the dearth of contextualized instructional materials (IM). This study aimed to generate the cultural funds of knowledge and translanguaging praxis of migrant fishers as bases for the development of contextualized IM. Under the lens of narrative ethnography, knowledge, beliefs, and practices of migrant fishers were documented in memory bank charts from six months of immersion in the coastal villages. Translingual narratives of purposively chosen participants were analyzed in the QDA Lite Miner software. Three translingual storybooks and teacher’s guides were developed, validated, evaluated, and pilot tested. It resulted to “very acceptable” for the storybooks and “excellent” rating for the teacher’s guides. The study recommends that school heads, teachers, and parents in the coastal villages may interact beyond the classroom setting and their indigenous knowledge will be used in the development of IM.